Weak signals of radicalisation in MSS: legal and psyco-social analysis - Salinas-de-Frías, Ana María (Comisión Europea, 2021)
Week signals of radicalisation is a concept borrowed from other fields which has been applied to countering radicalisation/terrorism in some MSS through specific practices. However, such a transposition can pose a number of problems as for its exact definition, scope and effects. Being weak means that these signals can hardly be discovered and properly analysed, some reasons that have pushed researchers and practitioners hand in hand and all over the EU to delve into how these weak signals materialise nowadays and ways to potentially predict derived actions so that the radicalisation proccess is not finally culminated or the terrorist attack is avoided. As an actual key threat EU MSS are very aware of, they have put much interest on the possibility of conceiving suitable systems for detecting and understanding them. The paper splits this main general question into three sub-questions: 1. What does the ‘weak signals’ concept mean, in particular when applied to terrorism/radicalisation? 2. In which manner have the three European States (Italy, Czech Republic & UK) applied the “weak signals” theory in their domestic policies for countering radicalization? Which have been their domestic initiatives? 3. Which challenges has the “weak signals” theory came across with regard to countering radicalization? An attempt to stablish advantages and disadvantages from a legal and psychological perspective. National experiences have been discussed in the framework of scientific theoretical considerations on the “weak signals” theory, according to an in-depth review of scientific literature on this topic with a view to an evaluation of shared practices. Since the preventative approach to combating violent extremism in general, and terrorism in particular, was adopted and prioritised, radicalisation prevention (RadPrev) has constituted a key concept. In fact, it has turned to be the cornerstone of international and national models for preventing terrorism. As radicalisation takes place before the terrorist offenses have been perpetrated, when successfully combatted, it would avoid terrorist attacks taking place. Hence, once States have opted for prioritising prevention of terrorism, radicalisation prevention has equally become a crucial aspect to be approached. With the emergence of the so called lone-wolves, preventing radicalisation has become even more important. The importance of weak signals and their relevance for RADPREV and CT purposes has become progressively more evident as online terrorists’ activities have shown important traits of future terrorist attacks; unfortunately, many times those clues have been discovered a posteriori, constituting one of the most important criticisms made to law enforcement agents (LEAS) and security forces after a terrorist attack takes place. Yet, difficulties in detecting those weak signals and adequately differentiating them from the context and the pollution they can provide can lead a decision-maker to misinterpreting or even ignoring those signals and the information conveyed by them. In this regard, the importance of the processes of judgement and evaluation of these signals has been underlined. Italian system of weak signals detection in prisons, the SAIRO tool and the UK's system have been analysed in the paper, that concludes with several recommendations to EU Member States.
Se trata de un documento de investigación solicitado por la CE en el marco de la RAN PS (Radicalisation Awareness Network, Policy Support branch), con el fin de estudiar los sistemas de prevención y detención de los signos de radicalización en la población civil y en la penitenciaria en particular, a fin de obtener conclusiones de potencial aplicación a todos los Estado miembro. Se trata de un documento con información sensible por lo que el acceso al mismo no está disponible.
Keywords: Radicalismo; Establecimientos penitenciarios; Weak signals; Radicalisation; Prision radicalisation; Leaking; Identification; Radicalisation awareness